Economic and environmental effects of border tax adjustments - Everett B. Peterson; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2007)
Taxing imports from regions which are not subject to climate policy and subsidizing exports into these regions have recently been proposed to address presumed negative effects of the EU Emissions Trading Scheme (EU ETS) on industry competitiveness and carbon leakage. This paper analyzes the economic and environmental effects of alternative border tax adjustment (BTA) mechanisms using an extended version of the GTAP-E model that explicitly includes domestic trade and transport margins. The BTAs are imposed on regions which have not committed to emission targets under the Kyoto Protocol or which failed to ratify the Kyoto Protocol. The analyses distinguish between effects of the BTAs on the EU15 countries and on the rest of the EU (REU). Likewise, the analyses single out the effects of climate policy with and without BTAs on domestic output changes which are due to changes in import competition and export competitiveness. Implementing a BTA whose power is equal to the percentage change in production costs in the energy-intensive sectors in the EU has different impacts for those sectors in the EU15 countries compared with the REU countries. In the EU15, the BTA effectively neutralizes import competition in the energy-intensive sectors while enhancing the export competitiveness of these sectors. Conversely, in the REU, the BTA is not effective in neutralizing increased import competition or decreased export competitiveness because the majority of trade by the REU is with countries/regions that are not included in the BTA. Overall, implementing a BTA has little effect on the marginal abatement costs of achieving the emission reductions in the Kyoto Protocol and does little in reducing carbon leakage.
urn:nbn:de:0011-n-559250
Keywords: 330; Border Tax Adjustment; Klimaschutz; Makroökonomischer Einfluss; Schätzung; Welt